2020
DOI: 10.3390/ani10040584
|View full text |Cite
|
Sign up to set email alerts
|

Yield Performance, Laying Behaviour Traits and Egg Quality of Purebred and Hybrid Hens Reared under Outdoor Conditions

Abstract: This study compared the yield performance, laying behavioural traits and egg quality of purebred and hybrid hens (from 28 until 44 weeks of age, considering four periods) reared under outdoor conditions. The four genotypes were reared on the same trial station, on four areas (one genotype/area), and under the same environmental conditions from hatching until the end of the trial. Italian dual-purpose purebred (Ermellinata di Rovigo—ER and Robusta maculata—RM) and hybrid (Hy-Line Brown—HB and Hy-Line White 36—H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 36 publications
3
23
1
2
Order By: Relevance
“…The egg inclusions detected in these breeds are higher than those reported for hybrid strains, which have been selected for this trait. In a previous trial carried out on ER and Robusta Maculata hens (Rizzi, 2020), the blood and meat spots were similar to those of this study. Eggs laid by other breeds showed egg inclusions similar or higher to those of this trial (Lordelo et al, 2020).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The egg inclusions detected in these breeds are higher than those reported for hybrid strains, which have been selected for this trait. In a previous trial carried out on ER and Robusta Maculata hens (Rizzi, 2020), the blood and meat spots were similar to those of this study. Eggs laid by other breeds showed egg inclusions similar or higher to those of this trial (Lordelo et al, 2020).…”
Section: Resultssupporting
confidence: 85%
“…A comparison with other trials is only possible for some traits, because it is difficult for others due to different environmental conditions during rearing and storaging of the eggs. At the beginning of egg production, the yolk:albumen ratio was similar to those of hybrid eggs (Philippe et al, 2020, Rizzi, 2020, where yolk is less than 50% albumen weight, but with age the ratio increased. Eggs laid by other Italian and Portuguese hen breeds showed higher yolk percentages and lower albumen percentages than those of this trial (Di Rosa et al, 2020, Lordelo et al, 2020.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…An important trait for the egg quality is the weight: the four genotypes produced eggs classifiable into different size classes, according to the EC regulation [ 26 ]: the ER and RM eggs were small size (<53 g) until 39 and 35 weeks of age, respectively, and then medium size (53–63 g); the hybrid eggs were medium size at all the ages. For the HB and HW hens, egg weights of large size (>73 g) were observed at 39 and 43 weeks of age, and at 9.3% and 5.2% of the daily production, respectively [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…A previous work compared the egg chemical composition and sensory profile of eggs laid by hybrid and purebred hens; it reported that the albumen height and HU of fresh and stored eggs were similar among hybrids and Italian breed Robusta maculata, whereas the stored eggs of Italian breed Ermellinata di Rovigo showed lower HU [ 18 ]. A recent work on the aforementioned genotypes studied hen’s behaviour at laying and the effect of age on the quality of fresh eggs throughout the laying cycle [ 19 ].…”
Section: Introductionmentioning
confidence: 99%